Rules, Roles, and Controls : Governance in Social Protection with an Application to Social Assistance - Bassett, Lucy; Giannozzi, Sara; Pop, Lucian; Ringold, Dena (World Bank, Washington, DC, 2013)
The paper develops an operational definition of governance that can be applied to social protection. The 2004 World Development Report (WDR) accountability framework acts as a starting point, defining accountability in terms of a set of principal?agent relationships between policymakers, providers, and citizens. Applying this framework to social protection, the paper looks at three broad areas where the Bank is involved in governance in social protection: rules of the game, including clear criteria for entry and exit of programs; roles and responsibilities, including defining accountability relationships and incentive frameworks across levels of government and institutions involved in social protection; and controls and accountability measures, including the broad set of implementation mechanisms and procedures for ensuring that 'the right benefit gets to the right person at the right time'. The paper applies this framework to social assistance policies and programs, reviews what is currently being done across the Bank in this area, and identifies future opportunities for clients and Bank engagement.